2020
DOI: 10.1080/09613218.2020.1770051
|View full text |Cite
|
Sign up to set email alerts
|

Holistic indoor environmental quality assessment as a driver in early building design

Abstract: Research and practice agree that decisions taken early in a project have a higher impact and are less costly. Current building performance assessment methods are not suited to accommodate the responsiveness required for early design processes and are often used for validation in the later stages where the feedback has little design impact. Tools developed specifically for early stage Design Decision Support (DDS) are either too simplistic, provide no solution to addressing combined indoor environmental quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 66 publications
(104 reference statements)
0
10
0
Order By: Relevance
“…However, in designing quality IE, keen consideration is given to the lighting, ventilation, orientation and energy consumption of the building and would thus require the expertise and opinions of the services engineer at the conceptualisation stage of the project (Olanipekun et al , 2018). This is in stark contrast to the traditional building method, where the services engineer is only introduced at the final stage of the design and is mandated to provide lighting, heating and cooling systems to the almost complete building (Rohde et al , 2020).…”
Section: Resultsmentioning
confidence: 99%
“…However, in designing quality IE, keen consideration is given to the lighting, ventilation, orientation and energy consumption of the building and would thus require the expertise and opinions of the services engineer at the conceptualisation stage of the project (Olanipekun et al , 2018). This is in stark contrast to the traditional building method, where the services engineer is only introduced at the final stage of the design and is mandated to provide lighting, heating and cooling systems to the almost complete building (Rohde et al , 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Kim and de Dear (2012) show that the relationship is not linear. A wide variety of assessment models have been developed (Heinzerling et al, 2013) which most recently aim for "holistic" assessments of IEQ (Leccese et al, 2021;Rohde et al, 2020). However, despite the name, the holistic IEQ assessment methods are, by their nature, confined to the four main parameters of IEQ-light, air quality, acoustics, and thermal comfort-thus not addressing other (universal) design-related aspects that can contribute to perceived comfort in buildings.…”
Section: Tools and Methods For Promoting Energy Efficiency And Univer...mentioning
confidence: 99%
“…Hence, DOSH (2019) suggested that these hazards can be avoided by planning construction sites in a secure location with no potential noise hazards. In addition, acoustic comfort can be improved through sound insulation of partition walls, ceiling panels and floor separation during the design phase (Rohde et al, 2021). According to Stavridou (2015), thermal comfort can contribute to an individual's health and well-being by creating a pleasant living environment.…”
Section: Environmental Design Parametermentioning
confidence: 99%
“…UBBL (2006) stated that each room must have natural lighting and ventilation provided by windows and unobstructed air flow to assist in accomplishing this. Rohde et al (2021) also suggested that exterior sun shading, suspended ceilings, load-bearing construction, and mechanical ventilation could also improve thermal comfort and reduce heat loss.…”
Section: Environmental Design Parametermentioning
confidence: 99%